Rhein Inhibits NF-κB Signaling Pathway to Alleviate Inflammatory Response and Oxidative Stress of Rats with Chronic Glomerulonephritis - Qian Chen; Hai Guo; JuanJuan Hu; Xiaofeng Zhao (Applied Bionics and Biomechanics)
Objective. To explore the effect and mechanism of rhein on chronic glomerulonephritis (CGN). Method. Twenty-four eight-week-old male SD rats were randomly divided into following 4 groups (6 rats in each group): control group, CGN group, rhein group, and benazepril (Ben) group. And 5 mg/mL of cationization-bovine serum albumin (C-BSA) was mixed with an equal volume of Freund’s incomplete adjuvant for the preparation of 2.5 mg/mL of C-BSA solution. The rat model of CGN was established by injection of C-BSA for six weeks. Calculation of the renal index in rats was conducted. Biochemical detection was performed to measure the level of 24 h urinary protein, blood urea nitrogen (BUN), serum creatinine (SCr), and serum albumin (ALB) of the rats, as well as the level of malondiadehyde (MDA), superoxide (SOD), and glutathione peroxidase (GSH-Px) in the kidney tissue. Hematoxylin and eosin (H&E) staining was utilized to measure histological changes in the kidney of the rats. The level of TNF-α, IL-1β, IL-6, and ICAM-1 in rat kidney tissues was determined by enzyme-linked immunosorbent assay (ELISA). Western blot was applied to check the expression of NF-κB in the nucleus and cytoplasm as well as the expression of IκBα and p-IκBα in rat kidney tissues. Results. Rhein could decline urinary protein, restore blood biochemical parameters, and protect renal tissue in rats with CGN. Besides, rhein could inhibit the activity of the NF-κB signaling pathway in rats with CGN and could alleviate the inflammatory response and oxidative stress level at the same time. Conclusion. Rhein alleviates inflammatory responses and oxidative stress in rats with CGN. It also provides a theoretical basis and data support for the therapeutic drugs for CGN.